2009
DOI: 10.1590/s1517-83822009000100006
|View full text |Cite
|
Sign up to set email alerts
|

Constitutive and inducible pectinolytic enzymes from Aspergillus flavipes FP-500 and their modulation by pH and carbon source

Abstract: Growth and enzymes production by Aspergillus flavipes FP-500 were evaluated on pectin, polygalacturonic acid, galacturonic acid, arabinose, rhamnose, xylose, glycerol and glucose at different initial pH values. We found that the strain produced exopectinases, endopectinases and pectin lyases. Exopectinases and pectin lyase were found to be produced at basal levels as constitutive enzymes and their production was modulated by the available carbon source and pH of culture medium and stimulated by the presence of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
10
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(16 citation statements)
references
References 27 publications
4
10
0
2
Order By: Relevance
“…The negative influence of the initial pH on endopectinase and exopectinase production by both Aspergillus strains (Table 2) was consistent with the results reported previously, where higher endopectinase and exopectinase production was obtained with an acidic pH medium for A. flavipes FP‐500 (Martínez‐Trujillo et al. 2009), Aspergillus oryzae (Malvessi and Moura da Silveira 2004) and A. niger (Shubakov and Elkina 2002).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The negative influence of the initial pH on endopectinase and exopectinase production by both Aspergillus strains (Table 2) was consistent with the results reported previously, where higher endopectinase and exopectinase production was obtained with an acidic pH medium for A. flavipes FP‐500 (Martínez‐Trujillo et al. 2009), Aspergillus oryzae (Malvessi and Moura da Silveira 2004) and A. niger (Shubakov and Elkina 2002).…”
Section: Discussionsupporting
confidence: 91%
“…2009), Aspergillus oryzae (Malvessi and Moura da Silveira 2004) and A. niger (Shubakov and Elkina 2002). On the other hand, the positive effect of the initial pH on pectin lyase production by A. flavipes FP‐500 was consistent with our previous findings (Martínez‐Trujillo et al. 2009), whereas for A. terreus FP‐370, the effect of this factor was not significant, although the corresponding R 2 value suggests that the effect of this factor could be negative (Table 2).…”
Section: Discussionsupporting
confidence: 90%
“…Alginate lyase production has also been reported to be influenced by the type of carbon source present in the environment (Fu et al 2008). Likewise, production of other carbohydrases including hemicellulases, pectinase and amylases is also inducible and wheat bran has been indicated to be a good inducer of these enzymes (Teixeira et al 2000;Martínez-Trujillo et al 2009;Irfan et al 2012;Singh et al 2014;Tallapragada and Venkatesh 2011), thereby indicating that the fungus can sense the availability of various carbohydrates in the environment and make the endogenous alterations to utilize those by production of various carbohydrases for its own benefit. In the study, effect of different metal salts was also studied and different enzymes were found to be induced maximally by different metal ions which are essential for the growth of fungi as they act as cofactors for various enzymes.…”
Section: Discussionmentioning
confidence: 99%
“…A similar model has been proposed in Aspergilli, where several TFs are involved and the expression profile of pectinolytic genes changes over time [70, 71, 143]. …”
Section: Transcription Factors Directly Involved In Plant Biomass Degmentioning
confidence: 99%